Obtención de términos energéticos : acoplamiento de Russell - Saunders - Flores Vásquez, Jaime A. (2001)
A first need for the interpretation of atomic spectra lead physicist and chemists towards a continuous development of models in order to understand the order, known as electronic configuration, within an atom. Since Bohr's model, it was accepted that a signa! in a spectrum corresponds to an electronic transition; nowadays the complexity of energy levels, generated by unpaired electrons in an orbital, can be understood in terms of L and S coupling in lighter atoms. This article details the extent of the use of such diagrams, expecting to be a reference in order to achieve the method and its results.